2018
DOI: 10.1126/scisignal.aao6847
|View full text |Cite
|
Sign up to set email alerts
|

A DGKζ-FoxO-ubiquitin proteolytic axis controls fiber size during skeletal muscle remodeling

Abstract: Skeletal muscle rapidly remodels in response to various stresses, and the resulting changes in muscle mass profoundly influence our health and quality of life. We identified a diacylglycerol kinase ζ (DGKζ)–mediated pathway that regulated muscle mass during remodeling. During mechanical overload, DGKζ abundance was increased and required for effective hypertrophy. DGKζ not only augmented anabolic responses but also suppressed ubiquitin-proteasome system (UPS)–dependent proteolysis. We found that DGKζ inhibited… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 49 publications
1
27
0
Order By: Relevance
“…Alterations in skeletal muscle mass are driven by changes in the balance between the rate of protein synthesis and protein degradation, and signaling by mTOR has been widely implicated in the regulation of protein synthesis (34)(35)(36). Consistent with this notion, several studies have shown that rapamycin can prevent the initial increase in protein synthesis that occurs in response to various forms of mechanical stimulation (9,(37)(38)(39).…”
Section: Raptor/mtorc1 Is Not Necessary For a Mechanical Overload-indmentioning
confidence: 87%
“…Alterations in skeletal muscle mass are driven by changes in the balance between the rate of protein synthesis and protein degradation, and signaling by mTOR has been widely implicated in the regulation of protein synthesis (34)(35)(36). Consistent with this notion, several studies have shown that rapamycin can prevent the initial increase in protein synthesis that occurs in response to various forms of mechanical stimulation (9,(37)(38)(39).…”
Section: Raptor/mtorc1 Is Not Necessary For a Mechanical Overload-indmentioning
confidence: 87%
“…The protein encoded by NAP1L1 controls chromatin compaction but has also been shown to bind to and regulate the nuclear-cytoplasmic shuttling of DGKζ 68 . Importantly, DGKζ was shown recently to play a pivotal role in mechanical overload-induced muscle hypertrophy in rodents, but only if the nuclear localization signal of DGKζ was intact 69 . While the nature of this interaction in humans warrants further investigation, the example attests to the hypothesis-generating power of transcriptome profiling and its inherent potential for biological discovery.…”
Section: Omic-based Science and Skeletal Muscle Hypertrophymentioning
confidence: 99%
“…Subcellular localization of DGKζ varies dramatically among different cell types. It has been shown to localize predominantly in the nucleus, in the cytosolic compartment, or distribute in both nucleus and cytosol dependent on different cell types and tissues examined [41,44,47,74‐77]. Our data indicate that DGKζ function is dynamically regulated in T cells via shuttling between the cytosol and nucleus and that nuclear localization of DGKζ serves as a negative control of DGKζ function by preventing it from accessing its substrate in the cytoplasmic membrane.…”
Section: Discussionmentioning
confidence: 73%
“…The nucleus contains different pools of DAG and nuclear DGKζ has been shown to reduce nuclear DAG concentration in HEK293 cells [44]. In the nucleus of skeletal muscle, nuclear DGKζ interacts with the class O of forkhead box transcription factor (FoxO) to mitigate FoxO‐mediated ubiquitin‐proteasome system dependent proteolysis to prevent muscle atrophy, which is independent on its kinase activity but dependent on its nuclear localization [77]. Whether nuclear DGKζ performs similar functions in T cells remains to be determined.…”
Section: Discussionmentioning
confidence: 99%